The dialogical-dialectical principle in Complex Planetary Decolonial Mathematics Education - Rodríguez, Milagros Elena (Educação Matemática Debate, 2023)
The dialogical-dialectical principle in Complex Planetary Decolonial Mathematics Education is analyzed; We emphasize the bonanzas of ecosophy and diatopy in this study, with the transmethod with comprehensive, ecosophical and diatopical hermeneutics in analytical, empirical and purposeful moments. Research in the lines of research: Paulo Freire: the wanderer of utopia in transmethodologies; planetary decoloniality — complexity in re-ligation; Complex Planetary Decolonial Mathematical Education and transepistemologies of knowledge-knowledge and transcomplex transmethodologies. In the propositive moment we show that the dialectic allows us to know each part of a mathematical problem, but the dialogical principle places us in the communication of those parts with the whole, their causes and effects when they overlap. For this reason, we move through the triad: order-disorder-organization that is not only antagonistic, but complementary, and it is in this dialectic of complementarity and antagonism that complexity is found.